2021
DOI: 10.1016/j.compedu.2021.104184
|View full text |Cite
|
Sign up to set email alerts
|

The mediating role of digital informal learning in the relationship between students' digital competence and their academic performance

Abstract: This article is made publicly available in the institutional repository of Wageningen University and Research, under the terms of article 25fa of the Dutch Copyright Act, also known as the Amendment Taverne. This has been done with explicit consent by the author.Article 25fa states that the author of a short scientific work funded either wholly or partially by Dutch public funds is entitled to make that work publicly available for no consideration following a reasonable period of time after the work was first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
54
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(87 citation statements)
references
References 98 publications
(152 reference statements)
6
54
0
7
Order By: Relevance
“…Finally, the data were analyzed using SEM to determine the relationship between the research variables. It should be noted that the data for this article is part of a larger data set—a part of it was used in this paper, and the other part was used in another paper by Mehrvarz et al (2021). [Corrections made on 23 June 2021, after first online publication: The preceding statement and reference details for Mehrvarz et al (2021) have been added in this version.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, the data were analyzed using SEM to determine the relationship between the research variables. It should be noted that the data for this article is part of a larger data set—a part of it was used in this paper, and the other part was used in another paper by Mehrvarz et al (2021). [Corrections made on 23 June 2021, after first online publication: The preceding statement and reference details for Mehrvarz et al (2021) have been added in this version.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown a positive relationship between ICT skills and academic competence in different contexts. For example, in higher education institutes, Mehrvarz, et al [ 121 ] pointed out that digital competence could affect academic performance. Yazon, et al [ 122 ] found that faculty’s digital literacy had a strong relationship with research output.…”
Section: Discussionmentioning
confidence: 99%
“…Los estudiantes, aunque están preparados tecnológicamente, presentan dificultades en la transferencia de las competencias digitales (ej. escritura en RS) a las competencias de escritura académica para integrar en los escritos que se les solicitan en sus asignaturas académicas o en sus productos de titulación como tesis o artículos académicos (Mehrvarz, et al, 2021). Más aún, diversos autores señalan una relación directamente positiva entre el éxito profesional-académico y las competencias de escritura académica (Katila, et al, 2020;Kiriakos & Tienari, 2018).…”
Section: Desarrollounclassified
“…En este sentido, la escritura académica digital se ha impulsado aún más en el contexto de la pandemia COVID-19, algunas de las investigaciones a nivel internacional señalan que el uso de softwares o plataformas digitales son herramientas de andamiaje valiosas para el desarrollo de competencia de escritura académica (Strobl et al, 2019). Otros estudios señalan la posibilidad de transferencia entre las composiciones escritas en Redes Sociales (RS) al ámbito de la escritura académica (Shepherd, 2018;Mehrvarz, et al, 2021).…”
Section: Introductionunclassified